Compact UWB Printed Slot Antenna with Three Extra Bands and WiMAX Rejection Functionality - Das, Amartya; Acharjee, Juin; Mandal, Kaushik (Společnost pro radioelektronické inženýrství, 2019)
A compact ultra-wideband (UWB) printed slot antenna with additional bands of 870-960 MHz, 1.67-1.84 GHz, 2.33-2.57 GHz for GSM-900, GSM-1800 and Bluetooth respectively along with WiMAX band rejection functionality at 3.27-4.02 GHz is presented for various wireless applications. A simple circular patch fed by a trapezoidal-shaped microstrip line is conceived to cover entire UWB (3-10.5 GHz). Three additional bands have been accommodated by incorporating two pairs of spider arm-shaped resonators at the top of the slotted ground. Coupling between the extended feed line and extended back resonator is used to acquire a stop band characteristic for the reduction of possible interference between WiMAX and UWB bands. Moreover, an arc-shaped resonator and a cross-shaped slot on the feed line are conceived to enhance the bandwidth of the UWB. The proposed design is simple in structure and compact with an overall dimension of 50×50×1.6 mm3, hence length is only 0.046λ with respect to the lower edge frequency (3 GHz) of the UWB. The simulated and measured results are in good agreement that ensures the potentiality of the proposed antenna structure for UWB and multiservice wireless applications.
Keywords: UWB; printed antenna; extra bands; band rejection; GSM-900; WiMAX